STRATEGI GASTRODIPLOMASI KOREA SELATAN SEBAGAI UPAYA NATION BRANDING DALAM MENINGKATKAN PENDAPATAN NEGARA DARI SEKTOR PARIWISATA PADA PERIODE 2015-2019 - M. Agung, (2023)
Globalization has created a borderless world without time and space boundaries. The international community has a access to information exchange easily due to significant developments in the field of information and communication technology. Actors in international relations, especially states, must be able to take advantage of this phenomenon to increase their influence to the international public. This is also coupled with the shifting of contemporary political issues from high politics to low politics. For this reason, the state must be able to adapt by switching to use its soft power instruments. One of the soft power instruments owned by a country is culture. Culture has a attractive power which can be used as a diplomatic tool to attract international public attention. Of the various cultural elements, food is considered to be the easiest cultural element to be accepted by foreign publics. For this reason, gastrodiplomacy exists as a new type of public diplomacy practice that uses food as its main instrument. South Korea is one of the countries in the world that has successfully used gastrodiplomacy to increase its influence and positive image in the eyes of the international community so that it has a positive impact on its tourism. Since the practice of gastrodiplomacy was carried out in 2009, South Korea's nation branding index has increased so that it is able to invite foreign tourist arrivals to come. With the increase in foreign tourist arrivals, South Korea's income from the tourism sector will also increase.